Rethinking Money - Daria Moiseeva; Olga Kuzina (Journal of Economic Sociology, 2022)
In his book The Social Life of Money, Nigel Dodd, a professor at the LSE, presents the results of his research on money. The main purpose of the book is to reconsider the nature of money, especially its social nature. The author explores the possibilities to change society by rethinking the existing economic, sociological, philosophical, psychological, anthropological, linguistic and other social science approaches to understanding money. Referring to the history of the origin of money, Dodd showed how the theories of the invention of money proposed by K. Menger, B. Laum, G. Simmel, M. Mauss, F. de Saussure, M. Agliette, and A. Orléan, shape our ideas about money and the ways of its social construction. Based on classical economic theories, the author challenges the role of money in the reproduction of social conflicts and inequality, as well as the relationship of money with credit and debt. Dodd describes how the transition from the perception of debt as a moral obligation to debt as a monetary obligation took place and the consequences of this transition. Writing about various aspects of the functioning of money, Dodd notes that for the completeness of the analysis it is important to understand how people solve the problem of managing an overabundance of money and how this determines the cultural aspects of the existence of money. He explains his sociological view on money and applies it to the analysis of the financial crisis of 2007–2008 and its consequences. The author discusses the sources of the crisis, describes theoretical perspectives that underpin the previous and existing financial systems, and suggests ways to possible positive transformation of money in the future by explaining several monetary utopias. The Social Life of Money is an example of thorough analytical and methodological accuracy and profound research on money in sociology. This book can be of high value both for experts whose research is focused on money and for anyone interested in the development of social theory today.